Complex interactions between benefits, ecosystem services and landscape dynamics: A synthesis of Lake Malombe, Malawi. Issue 1 (26th December 2021) - Makwinja, Rodgers; Mengistou, Seyoum; Kaunda, Emmanuel; Alamirew, Tena
Abstract: African inland freshwater lakes experience a high level of exploitation, as evidenced by a decline in biodiversity, food production and rising poverty. Lake Malombe in Malawi provides the best example of this situation. The lake catchment is severely degraded and faces profound biodiversity losses. Households in the catchment are caught in a vicious cycle of poverty. Management decisions regarding Lake Malombe involve choices that reflect opportunity costs among the complex socio‐ecological interactions that are often unnoticeable. Ecosystem managers unintentionally make decisions that diminish the value of some critical ecosystem services (ESs), while enhancing others. The present study used geospatial and participatory approaches to explore complex interactions between benefits, ESs and landscape dynamics. The study findings indicate the ecosystem provisioning services (EPSs) are the main livelihood sustenance vehicle for Lake Malombe's local population. The increased cultivated land from 52, 932 to 78, 983 ha and decreased forest land from 56, 235 to 8585 ha between 1989 and 2019 are linked to EPSs changes at the expense of regulatory, supporting and cultural ecosystem services. The findings of the present study suggest an important need to balance the opportunity costs among the complex ESs dynamics and landscape transformation as a means of achieving management policy efficiency while at the same time also avoiding adverse outcomes from human activities.